Phase 1 study of safety, tolerability, and efficacy of intradermal DNA vaccine ASP2390 in adults allergic to house dust mites - Thomas Kayser, MD, BS; Ronald Smulders, MD, PhD; Tomohiro Kusawake, PhD; Erik Wambre, PhD; Gurunadh R. Chichili, PhD; Mary B. Blauwet, DrPH; Anna Spence, MS; Melanie Patton, BS; Rima Tabash, PhD; Hannah A. DeBerg, PhD; Sugandhika Khosa, MS; Philipp Badorrek, MD; et al. (Journal of Allergy and Clinical Immunology: Global)
Background: House dust mite (HDM) allergies are prevalent, yet current treatments like allergen avoidance, pharmacotherapy, and conventional allergen immunotherapy present limitations. The novel LAMP (lysosomal-associated membrane protein)-based DNA vaccine ASP2390 targets major HDM allergens, potentially shifting immune responses toward nonallergic pathways and minimizing the risk of atopy, with positive safety and efficacy signals in preclinical models. Objective: We evaluated the safety, tolerability, and efficacy of first-in-human intradermal ASP2390 in adults with HDM allergy. Methods: A randomized, double-blind, placebo-controlled phase 1 trial was conducted in adults with HDM-induced allergic rhinitis. Participants received either 1 mg or 4 mg of ASP2390 or placebo intradermally once weekly for 12 weeks, with safety, tolerability, and pharmacodynamic responses assessed over a 63-week period, including early-phase clinical effects assessed via HDM exposure in an allergen challenge chamber. Results: Twenty-eight adults (mean age, 26.9 years; 23 male participants), with 7 receiving 1 mg and 13 receiving 4 mg ASP2390, 8 receiving placebo, showed no serious adverse events or withdrawals due to treatment-emergent adverse events. The most common events were nasopharyngitis, coronavirus disease 2019, headache, fatigue, and diarrhea; fatigue and headache were the most frequent systemic reactions, and injection-site tenderness the most frequent local reaction. There were no substantial changes in allergen-specific immunoglobulin levels, basophil activation, or T helper cell subpopulations, and no difference in allergic clinical responses compared to placebo. Conclusion: Intradermal DNA vaccine ASP2390 is safe and well tolerated but does not show an immunologic or clinical response in a small sample of adults allergic to HDM.